Does the Hospital Day of Surgery for Endovascular Repair of Symptomatic Abdominal Aortic Aneurysms Affect Outcomes?. (April 2023) - Dauer, Marc J.; Friedmann, Patricia; Parides, Michael; Lipsitz, Evan; Indes, Jeffrey; Teo, Richard; Koleilat, Issam
Objective: Symptomatic abdominal aortic aneurysms (sAAA) are considered surgically urgent. Recent data suggest delaying surgery allows for medical optimization without affecting outcomes. We investigated the association of the hospital day of surgery with 30 day outcomes. Methods: Patients with infrarenal sAAA undergoing endovascular aortic repair (EVAR) between 2011 and 2018 in the American College of Surgeons National Surgery Quality Improvement Project database were included. The primary outcome was 30 day mortality. Additional outcomes included myocardial infarction, pulmonary complications, length of stay, and discharge disposition. Days-to-surgery were classified as the day of presentation (D0), day 1, day 2, days 3 and 4, days 5 to 7 (D5), and day 8 or more (D8). Results: A total of 804 patients were identified. D8 patients had higher proportions of dyspnea on exertion, chronic obstructive pulmonary disease, congestive heart failure, and history of dialysis. D0 surgery appeared protective of mortality (odds ratio [OR] 0.34, p=0.0132). Each additional day increased the mortality risk (OR 1.23, p<0.001) although not within the first 4 days. There was increased mortality for patients having surgery at D5 (7.7%) and D8 (23.8%) compared with repair earlier (1%–4%, p=0.03). Bivariable analysis revealed no significant differences in secondary outcomes. Multivariable modeling revealed increased mortality for D8 versus D0 (adjusted OR of 6.8, 95% confidence interval 1.7–26.5). Conclusions: While D0 appears to have the lowest risk of mortality, EVAR for sAAA up to 4 days may not be associated with increased mortality. Further research should determine delay etiologies and whether they improve operative planning and optimization without impacting morbidity and mortality.